Caracterização molecular de genes do sistema imune de búfalo - Borges, Mariana Maciel [UNESP] (2014)
In mammals, genes related to immune response to pathogens are organized in a genomic region named Major Histocompatibility Complex (MHC). MHC genes are also involved in mate-choice, occurrence of spontaneous abortions and maintenance of pregnancy. The existence of a genomic library, constructed with buffalo genome, allows the characterization of MHC genes, providing sources for understanding the mechanisms involved in resistance/susceptibility to diseases and in reproduction, contributing for annotation of these genes on buffalo genome. To determine the molecular structure of buffalo immune system genes, the present study aimed to identify and characterize clones containing class IIb markers from a buffalo genomic library. Selection of clones was performed by PCR technique, according to three-dimensional system (superpool, singlepool, row/column system) in which clones are arranged. To identify the clones were used 21 class IIb markers, previously mapped on buffalo chromosome 2. Among the 33.792 clones evaluated, three clones were identified for the MHC markers 11.05, 12.05, 13.00 and DMA. These clones were then purified and sequenced by pyrosequencing, presenting insert size ranging from 26 to 117 Kb. Each clone sequence were aligned with two bovine genome assemblies (UMD_3.1 and Btau_4.6.1), where the most significant alignments were identified with the corresponding sequences to BTA23. Sequences of both clones showed a greater coverage in UMD_3.1 assembly. Four genes were predicted for clone A/17 DNA sequence (H2B, DMB, DMA and BRD2), and one gene (VPS52) was predicted for clone I/09 sequence. Each gene had the number and size of exons and introns determined. The identification of repetitive sequences showed that 49,3% of clone A/17 sequence and 46,3% of clone I/09 sequence are represented by transposable elements. Furthermore, small RNA sequences were identified in both clones ...